The I-Ork project: a technological approach to inclusive music making and therapy - Marcella Mandanici; Giuseppe Bergamino; Sara Valente (Frontiers in Education)
The “Inclusive Orchestra” project (I-Ork) examines the issues concerning inclusive music making and therapy from a multidisciplinary perspective, involving music technology, human-computer interaction, customized music instrument design, music therapy practices, community music making, music education and musical creativity. The core objective is to foster the creation of performance groups composed of individuals with diverse abilities, including those with physical and/or cognitive impairments, as well as participants with no formal musical background. The research team iteratively designed several digital musical instruments and performance setups, tested during sessions involving individuals with various disabilities. A specific observational protocol based on the Individualized Music Therapy Assessment Profile (IMTAP) was developed and applied to validate the effectiveness of the study. This protocol allowed for a structured assessment of participants' behavior across functional, emotional, and musical domains. Preliminary results indicate that the digital instruments promote high levels of participation, elicit positive emotional responses, stimulate curiosity, and support exploratory behavior. The findings suggest that technology-enhanced musical tools can play a significant role in inclusive music practices by enhancing accessibility, engagement, and emotional expression. The IMTAP-based evaluations provided valuable insights into how different instruments align with users' needs, supporting further refinement of both the tools and intervention strategies.